Evolução dos serviços ecossistêmicos em diferentes estágios de regeneração natural - Pereira, Luara Castilho (2020)
Forests are important for several ecosystem services that bring benefits to man, mainly support services, such as nutrient cycling, climate mitigation, erosion control, water resource recharge, among others. Therefore, the importance of the sustainability of this resource for the perpetuation of species is remarkable. One of the most efficient techniques for restoring natural ecological conditions is natural regeneration. It is known that certain regions have difficulties in maintaining soil moisture to facilitate the process of gradual infiltration, however, forests have their own mechanisms to assist these conditions, such as the interception of water by the litter, to make the water gradually available to the soil. , soil moisture, compaction and density are also related to the process of passing water from the surface into the soil. This work sought to analyze the influence of natural regeneration on the environmental variables responsible for ecosystem support services. The project was installed in a RPPN in the Cerrado of São Paulo, with 3 fragments in different phases of natural regeneration (46 years, 13 years and 5 years), where over 12 months, monthly data of Net Precipitation (PE), Capacity of litter water retention (CRH), soil density (DS), soil moisture (US), mechanical resistance to soil penetration (RP), basic infiltration speed (VBI), hydraulic soil conductivity (K). CRH was inversely correlated with the net precipitation of the forest, the oldest area had the highest production and CRH of the amorphous material (in the most advanced stage of decomposition), despite not having the highest total CRH, it had the highest retention effective water content of litter. The older the regeneration, the larger the US and the lower the DS and the PR, showing that the regeneration promotes the improvement of the physical characteristics of the soil. Despite the VBI results being slightly below those found in the literature, this is not due to K, which presented values close to those in the literature, but rather due to soil water repellency, a characteristic present in the 3 fragments, so that the older the regeneration, the lower the repellency, showing that this characteristic present in semi-arid and sandy regions can be mitigated through natural regeneration. Finally, a correspondence analysis was carried out in order to explain the species distribution according to the environmental variables, with CRH and US being the most related to the species distribution. Thus, natural regeneration promotes improvement in environmental variables responsible for ecosystem support services.